PENGAWASAN KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI DUMAI DALAM RANGKA PELAYANAN EKSPOR TAHUN 2011-2013 - Febi Sabrina; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Problems that occur by monitoring the implementation of the Office of Surveillance and Customs and Excise ( KPPBC ) Type Madya B Dumai namely the lack of customs employees, this not optimal control KPPBC TMP B Dumai in export services both in the office and in the field such as the discovery of smuggling illegal goods and reduced foreign exchange in recent months. This type of research used in this research is descriptive qualitative approach . This research was conducted in Dumai where this area there are several official ports and harbors are still vulnerable people smuggling illegal goods. While the data collection by using the technique of interviewing informants were competent in their field as well as by direct observation in the field and documentation writers.This research found the smuggling of illegal goods from Malaysia and services provided by KPPBC TMP B Dumai to service users is still not optimal. Supervision Office of Surveillance and Customs and Excise Dumai in Export Services Framework is not maximized due to the implementation of effective oversight yet that is the size and standard of supervision is still weak, not maximum deviation assessment and correction work that is not running. Factors that hinder the implementation of supervision by KPPBC TMP B Dumai occur due to weak supervision in the field, a lack of human resources experts in the field of customs as well as wide area surveillance in Dumai. We recommend that the Office of Surveillance and Customs and Excise TMP B Dumai further increase the number of employees or officers of customs and excise in order to support the monitoring in KPPBC Dumai.Keywords : Surveillance , Office of Surveillance and Customs and Excise.